Fight load index and body composition are most associated with combat fitness in female Marines. Issue 4 (April 2019) - Allison, Katelyn Fleishman; Keenan, Karen A.; Lovalekar, Mita; Mi, Qi; Beals, Kim; Coleman, Lt. Col. Lawrence C.; Nindl, Bradley C.
Abstract: Optimizing tactical fitness is important for combat readiness and injury prevention, especially as women have entered ground combat military occupational specialties. Objectives: To assess characteristics of male and female Marines by Combat Fitness Test (CFT) performance clusters. Design: Cross-sectional study. Methods: Anthropometric, body composition (BF%, fat and fat-free mass [FM and FFM], and Fight load index [FLI], physiological (maximal oxygen uptake, lactate threshold and anaerobic power/capacity), and musculoskeletal (isokinetic strength of the knee, shoulder, torso, and isometric strength of the ankle) assessments were obtained from 294 male (M) and female (F) Marines. Hierarchical cluster analysis classified Marines based on performance of two CFT events (sec): Maneuver Under Fire (MANUF) and Movement to Contact (MTC). Following tests for normality, one-way ANOVA or Kruskal Wallis tests, followed by Bonferroni post-hoc tests, assessed characteristics across clusters and sex (alpha = 0.05). Results: Two clusters (C) were determined: C1: N = 66F, 16M and C2: N = 18F, 194M, with C2 demonstrating better performance on the MANUF and MTC. C1F demonstrated significantly greater BF% and FLI than C1M, C2F, and C2M. C2M demonstrated significantly greater knee flexion strength than C1F and C2F, but C1M was only significantly greater than C1F. C2M demonstrated significantly greater ankle eversion and inversion strength than C1F. Conclusions: Women with increased BF%, increased FM and reduced FFM relative to a fighting load may have decreased performance in combat-related tasks. Training programs based on an individual Marine's baseline body composition and fitness characteristics can enhance combat fitness and force readiness.